PENGARUH MOTIVASI, LINGKUNGAN KERJA DAN DISIPLIN KERJA TERHADAP KINERJA TENAGA KONTRAK (STUDI KASUS PADA RSJ MUTIARA SUKMA) - AHYAT, MUHAMAD; AGUSTINA, FITRIA IKA; AFRIWAN, OKKY; HAMZAH, HAMZAH (Universitas Mahasaraswati K. Mataram, 2024)
This study aims to determine the effect of work motivation, work environment and work discipline on the performance of contract workers at Mutiara Sukma Hospital, Prov. NTB. This research was conducted at Mutiara Sukma Hospital with a total of 68 respondents. To determine the contribution of motivational factors, environment, work discipline to the performance of contract workers, the determinant formula (R2) is used. After analyzing the questionnaire, the regression equation Y = 2.079 + 0.308X1 + 0.103 X2 + 0.632X3 is obtained. Furthermore, the value of the determinant coefficient (R2) of 0.742 is obtained, which means that the variables of motivation, environment and work discipline affect employee performance by 74.2% and the remaining 25.8% is influenced by other factors. To test the hypothesis in this study, the F test was used with a value F count = 61.322, and Ftable = 3.138 then Ha is accepted. This means that there is a positive influence between the variables of work motivation, work environment and work discipline simultaneously on the performance of contract workers at Mutiara Sukma Hospital. T test at a significant level of 95% and α = 0.05 obtained a T table value of 1.998, and T count for X1 = 3.211, X2 = 1.305, and X3 = 5.385. So the variables X1, X3 have a positive and significant partial effect on performance with T count > T table. Meanwhile, variable X2 and has a negative effect and does not fully have a significant effect on employee performance Tcount < Ttable.